Centrifuge testing to verify scaling of offshore pipeline ploughs. Issue 6 (14th November 2018) - Robinson, Scott; Brown, Michael John; Matsui, Hidetake; Brennan, Andrew; Augarde, Charles; Coombs, Will; Cortis, Michael
Abstract : Offshore pipeline ploughs have previously been modelled at 1 g with small 1:50 scale models designed to derive the parameters required for prediction of ploughing in terms of tow force requirements and potential advance rates. This was scaled up to prototype with the validity of the scaling verified through 'modelling of models' and with comparison to typical prototype tow forces but without direct validation. To allow further validation, a long centrifuge box and actuation system was developed for use on a medium-sized beam centrifuge. Previous approaches to 1 g ploughing were also improved through the use of micro-electro-mechanical systems accelerometers and new low-cost surface scanning techniques. A wide range of ploughing velocities were explored through increasing actuation speeds and the use of pore fluids of different viscosities. The study has shown that although there may be initial concerns over low effective stress scaling issues at 1 g, in shallow problems with small-scale models, the large deformation nature of the ploughing problem can be replicated with appropriate scaling. This allows the use of 1 g modelling for more efficient parametric studies for this application and has given further confidence to performance parameters for prototype modelling derived from 1 g and centrifuge studies.